Development of the Methodology for the Economic Evaluation of Managerial Decisions as a Factor of Economic Security Increase - Olga Aleksandrovna Romanova; Vladimir Yevgenyevich Strovskiy (Экономика региона, 2016)
In the article, it is noted that the emergence of the phenomenon of interdependence between security and development — so-called security-development nexus, becomes determining during the development of strategic documents at all hierarchical levels. It gives relevance to the search of the methodological decisions allowing to consider the possible threats to economic security at the strategic level, and the pragmatical actions which are not contradicting a strategic vector of economic entities development — at the tactical level. Instability factors which threat the economic security are revealed. A rationale for the development of the new model of national economy development, whose central element is new industrialization, is substantiated. The most important trends of the development of world economy influencing the strategic vector of the increase of the Russian economic security are considered. It is discovered that in the conditions of new industrialization, the intellectual core of the high-technology sector of the economy is formed by convergent technologies (NBICS technology). A methodological approach to the economic evaluation of management decisions in the conditions of uncertainty is offered. The methodological principles, which have to be accounted in the case of the development of the modern methodology for the economic evaluation of economic decisions, are allocated. Among them, there are the development of the preferred reality or so-called «vision of the future», the priority of network decisions as the basis for new markets development; the mass customization and individualization of requirements, basic changes of the profile of competences which provides the competitiveness in the labour market, use of the ideology of the inclusive development and reformative investment creating general values. The offered methodology is based on an optimum combination of the traditional methods of the economic evaluation of managerial decisions with the method of real option, reflexive estimates taking into account entropy as a measure of uncertainty. The offered methodological approach was tested for the development of mining and metallurgy of the Urals.